It's time to close the chapter - Darshan Singh, Ranjit Singh (Sunday Star, 2013)
THE Philippines Government officially announced their claim to North Borneo(now Sabah) on June 22,1962. Despite numerous attempts to settle the issue, it still festers on, exemplified by the latest tragic events unfolding on the east coast of Sabah.